ENRGISE: PRIMARY, SECONDARY, AND SAFETY RESULTS. (11th November 2018) - Pahor, M; Pahor, M; Manini, T; Anton, S D; Tracy, R P; Newman, A B; McDermott, M M; Ambrosius, W T
Abstract: The ENRGISE Pilot study has excellent retention and adherence. As of March 6, 2018 of the 286 randomized participants 97.2%, 98.2%, 95.5%, 89.8% have completed a 3, 6, 9, and 12 month follow-up visit, respectively, and 7.9% have a pending 12 month visit. A total of 88% of 234 participants randomized to omega 3 arms and 69% of 101 participants randomized to losartan arms reported excellent, very good, or good ability to take the study drugs. The DSMB did not raise any concerns regarding safety and recommended continuation of the study. Follow-up visits will be completed in June 2018. We will present the following outcomes according to the randomized arms: IL-6, 400 m walking speed, incidence of major mobility disability (inability to walk 400m), short physical performance battery scores (balance, 4 m walk, and chair stands tests), and strength. The pilot will inform the planning of the main ENRGISE trial.